Effect of copper refining on spatial distribution of heavy metal in surrounding soils and crops - JIANG Li-ying; YANG Xiao-e; YE Hai-bo; SHI Wei-yong; JIANG Yu-geng (浙江大学学报. 农业与生命科学版, 2002)
Investigation and analysis of soils and plants in the heavily polluted farm field near a smelting factory showed that the main elements in the pollutant included As, Cd, Cu, Pb and Zn, among which Cu, Pb and Zn content in soil were very high, reaching 1775.6, 1140.1 and 621.3 mg/kg respectively; The metal content in the soil decreased with increasing distance from the smelting factory and reached normal level at a distance of about 300 m. Heavy metal concentrations were relatively high at the surface soil layer (15 cm), and decreased with increasing soil depth. Soil microbial carbon content of surface layer was closely related to the concentration of heavy-metal in soils. For the purpose amendment, some agricultural measures were adopted in a field experiment, which effectively reduced available heavy metal content in the soil and increased the crop yield. However, following these treatments, the heavy metal concentrations of grains did not attained the national sanitary standards.